FACTORS RELATED TO THE INCIDENCE OF MEASLES IN CHILDREN AGED 12 – 59 MONTHS IN THE WORKING AREA OF THE TIRTAYASA HEALTH CENTER, SERANG REGENCY IN 2023 - Ratnasati; Lukman Waris; Rita Ramayulis (ZILLZELL MEDIA PRIMA, 2024)
This thesis aims to determine the factors related to the incidence of measles in the working area of the Tirtayasa Health Center, Serang Regency in 2023. The variables used consisted of independent variables consisting of: child factors (gender, measles immunization status, nutritional status, complete basic immunization status, status of high-dose vitamin A supplements), maternal factors (education level, level of knowledge, employment status, attitude), father factors (education level, employment status), environmental factors (occupancy density, house ventilation) and economic socialization factors (family income). The sample was mothers who had children aged 12 months to 59 months as many as 100 people and data was collected by distributing questionnaires. The results showed factors that were not associated with the incidence of measles: the sex of the child with a Pvalue of 0.427, the status of high-dose vitamin A supplementation with a Pvalue of 0.982, the employment status of the mother with a Pvalue of 0.950, and the employment status of the father with a Pvalue of 0.878. While the factors that are significantly related to the1 incidence of measles include: measles immunization status with Pvalue 0.000, nutritional status with Pvalue 0.026, maternal education level with Pvalue 0.000, maternal knowledge level with Pvalue 0.017, maternal attitude with Pvalue 0.006, father's education level towards with a Pvalue of 0.044, a density of a house with a Pvalue of 0.02, home ventilation with a Pvalue of 0.035 and family income against the incidence of measles Pvalue of 0.001. In accordance with the results of the study, the researchers' suggestions are: puskesmas officers to increase counseling, puskesmas to collaborate with other parties to improve the living environment and explore other variables for further researchers.